Determining the Shezi Coefficient Under Regulated Water Flow Conditions - Mirzaev, Mirzabek; Ibragimov Ilhom; Inomov Dilmurod (Indonesian Journal Publisher, 2026)
In the lower reaches of the Amu Darya River, the hydraulic regime has been significantly transformed under regulated flow conditions. The determination of the Chezy coefficient plays a crucial role in analyzing the kinematics and hydraulic resistance of the river flow. Based on field data obtained from Tuyamuyin, Kipchak, Niyetbaytas, Samanbay, and Kiziljar hydroposts, empirical relationships between the Chezy coefficient, discharge, and morphological parameters were developed. The analysis revealed that conventional formulas proposed by Manning, Forchheimer, Pavlovskiy, Agroskin, and Jeleznyakov showed considerable deviations under regulated conditions due to nonuniform depth distribution and increased roughness coefficients. The derived relationship for the lower Amu Darya provides improved accuracy in estimating the Chezy coefficient compared to classical methods. This approach enhances hydraulic computations and offers a practical basis for riverbed regulation and hydraulic design in managed flow conditions.